2006
DOI: 10.1182/blood-2006-07-037754
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 2 gene transcription is regulated by Ikaros-induced changes in histone acetylation in anergic T cells

Abstract: In T cells anergy may be evoked by an unbalanced stimulation of the T-cell receptor in the absence of costimulation. Anergic T cells are unresponsive to new antigen receptor engagement and do not produce interleukin 2. We present evidence that anergizing stimuli induce changes in histone acetylation, which mediates transcriptional repression of interleukin 2 expression. In response to calcium signaling, anergic T cells up-regulate the expression of Ikaros, a zinc finger transcription factor essential for lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
132
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(146 citation statements)
references
References 50 publications
11
132
1
1
Order By: Relevance
“…Previous studies have identified several genes that are upregulated in anergic CD4 + T cells when there is NFAT but not AP-1 transcriptional activation (20)(21)(22)(23)(24)(25)(26)(27). We therefore determined whether Sirt1, as a HDAC, induces and/or maintains CD4 + T cell tolerance by altering the expression of these anergic genes.…”
Section: Sirt1 Suppresses T Cell-dependent Immunity In Micementioning
confidence: 97%
“…Previous studies have identified several genes that are upregulated in anergic CD4 + T cells when there is NFAT but not AP-1 transcriptional activation (20)(21)(22)(23)(24)(25)(26)(27). We therefore determined whether Sirt1, as a HDAC, induces and/or maintains CD4 + T cell tolerance by altering the expression of these anergic genes.…”
Section: Sirt1 Suppresses T Cell-dependent Immunity In Micementioning
confidence: 97%
“…Anergy-associated genes are different from those genes activated during a productive immune response, and therefore their expression must be regulated by different transcriptional complexes (9,26,27). These genes include, among others, several E3 ubiquitin ligases, such as Cblb, Itch, and Grail; transcription factors, such as Egr2, Egr3, and Ikaros; Caspase3; and diacylglycerol kinase  (Dgka) (9,(28)(29)(30)(31)(32)(33)(34)(35). The expression of many of these genes seems to be controlled by NFAT, as their expression is drastically reduced in T cells that lack NFAT1 (9).…”
mentioning
confidence: 99%
“…Aiolos is a transcription factor of the Ikaros family involved in the development of lymphoid cell lineages (5,29,46) through different mechanisms, for example the regulation of the epigenetic status of target genes (47)(48)(49). In human Treg cells, for instance, FoxP3 and Aiolos form a heterodimeric complex that binds the Il2 promoter and suppresses IL-2 expression (29).…”
Section: Ahr-dependent Immune Cell Regulationmentioning
confidence: 99%